Edukasi Kesehatan Reproduksi dan Psikoedukasi Pergaulan Bebas sebagai Upaya Preventif Infeksi Menular Seksual (IMS) pada Remaja Angkatan Muda Gereja Protestan Maluku, Cabang Asos Jemaat GPM Karseka - Sumarah Suryaningrum; Marthen Luther Soplera; Louvenska Latupeirissa; Bintang Lony Vera Victory; Rufiati Simal; Hizkia G. Mautang; Frans Selfanay (Abdimas Indonesian Journal, 2026)
Adolescence is a critical transitional phase in the human developmental cycle, characterised by significant changes in biological, psychological, and social aspects. Biologically speaking, adolescents go through puberty, which triggers the maturation of the reproductive organs. However, this rapid physical development is often not accompanied by adequate health literacy, meaning that many adolescents do not yet understand how to properly maintain the hygiene and function of their vital organs. This lack of understanding regarding reproductive function is exacerbated by social dynamics such as promiscuity. The most concerning impact of the combination of lack of health information and promiscuity is the rising rate of Sexually Transmitted Infections (STIs) among the younger generation. Therefore, comprehensive education on reproductive health and the instilling of moral and spiritual values are crucial. The primary target of this initiative is the youth of the Maluku Protestant Church, Asos Branch of the GPM Karseka Congregation, to enhance understanding of reproductive health and the prevention of Sexually Transmitted Infections (STIs).